Peningkatan Daya Saing UMKM Dalam Menembus Pasar Ekspor - Ristanti Ristanti; Yuli Arisanti; Agung Sulistyo (CV. Kurnia Grup, 2024)
MSMEs play a crucial role in supporting the tourism industry. This condition is a great opportunity for MSMEs. The target market for MSMEs is not only local tourists but also foreign tourists. In reality, there is competitive competition on the ground. This condition affects not only local MSMEs but also foreign business actors. Numerous studies confirm that the Ansoff Model can facilitate the development of development plans. However, there has been little research in the MSME export area. This research contributes to increasing product competitiveness in export markets. This study uses a mixed research design (mix method). This research employed both interview activities and the distribution of questionnaires. The first stage involved distributing questionnaires to nine MSMEs that had carried out export activities. We carried out instrument mapping through internal factor evaluation (IFE), external factor evaluation (EFE), and SWOT analysis. The Internal Factor Evaluation (IFE) analysis reveals a positive difference value of 1.25. The strengths are greater than the weaknesses. The External Factor Evaluation (EFE) analysis reveals a positive difference score of 0.95. The opportunities that an organization has are greater than the threats. The Ansoff Model reveals market penetration as a viable strategy. MSME players need to pay attention to their target market. Global markets are more complicated because they involve different rules. Furthermore, MSME players need to consider the market opportunities they have. We must introduce the product's quality and characteristics on a large scale. The accuracy with which MSME actors analyze situations enables them to compete in any market.